2022
DOI: 10.3389/fimmu.2022.854724
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics of Immune Cells Reveal Diversity and Exhaustion Signatures in Non-Small-Cell Lung Cancer

Abstract: Understanding immune cell phenotypes in the tumor microenvironment (TME) is essential for explaining and predicting progression of non-small cell lung cancer (NSCLC) and its response to immunotherapy. Here we describe the single-cell transcriptomics of CD45+ immune cells from tumors, normal tissues and blood of NSCLC patients. We identified three clusters of immune cells exerting immunosuppressive effects: CD8+ T cells with exhausted phenotype, tumor-associated macrophages (TAMs) with a pro-inflammatory M2 phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…TEX-related genes can be extracted from CD8TEX cells from the scRNA-seq database. Additionally, TEX-based gene signatures have been widely used to predict prognostic, molecular, and immune features, as well as therapeutic responses in several tumors, including LIHC, lung adenocarcinoma, and NSCLC [ 34 , 35 , 36 , 37 ]. In this study, we identified and validated a TEX-related signature for predicting the prognosis and immune response in PACA using integrated analysis of scRNA-seq and bulk RNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…TEX-related genes can be extracted from CD8TEX cells from the scRNA-seq database. Additionally, TEX-based gene signatures have been widely used to predict prognostic, molecular, and immune features, as well as therapeutic responses in several tumors, including LIHC, lung adenocarcinoma, and NSCLC [ 34 , 35 , 36 , 37 ]. In this study, we identified and validated a TEX-related signature for predicting the prognosis and immune response in PACA using integrated analysis of scRNA-seq and bulk RNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%